Tourism and the Economy of Nigeria: A synthesis of its contributions to GDP from 2005-2016 - Alamai, Murtala Mohammed; Hussaini, Mohammed Uwais; Fatima, Aliyu Ladi (Advances in Social Sciences Research Journal, 2018)
For many emerging economies tourism is the export earner, including several Least Developed Countries (LDCs) such as Burkina Faso, Gambia, and Nigeria because tourism has proved to be a strong and resilient economic activity that contributes to the economic recovery of nations through generation of billions of dollars in income while also stimulating job creation for destinations across the globe. In view of that, this paper is a theoretical review of the direct, indirect and induced impact of tourism to the economic development of Nigeria over a period of 16 years from the emergence of the millennials. The paper observes that Nigeria as a country has the potentials of making tourism a main source of its earnings being that it has a diverse tourist attractions, a large domestic tourist market, an upcoming middle class which can reinvigorate domestic tourism and unique cultural settings capable of enticing foreign tourists though there is no political will to implement and sustain its tourism policies and actions which can translate into economic gains for its citizens. The paper recommends among other things the entrenchment of sound tourism development master plan capable of rejuvenating the potentials in the economic blueprint of the country and ensuring sustainable tourism development participation even in the face of difficulties and uncertainties. The paper employs the Desk Study approach as its methodology.